1967
DOI: 10.1139/f67-103
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Hypothetical Age of the Newfoundland Bait Squid Illex illecebrosus illecebrosus

Abstract: Length measurements of a migrant ommastrephid squid Illex illecebrosus illecebrosus (Le-Sueur), in Newfoundland east coast waters indicated that only one modal class was present except in November of some years. Average lengths and weights of random samples taken monthly from May to November indicated also that growth was very rapid during this period. The majority of the population, averaging 140 mm in mantle length (54 g whole weight) in both sexes in May, reached maximum mantle lengths of 260 mm in males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Unlike males, females do not reach maturity in Newfoundland waters prior to their autumn migration (Squires, 1967;Mercer, 1973). In addition to aiding in migration, a larger body size may provide a reproductive benefit as postulated for I. argentinus, for which fecundity has been shown to increase with mantle length (Laptikhovsky and Nigmatullin, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike males, females do not reach maturity in Newfoundland waters prior to their autumn migration (Squires, 1967;Mercer, 1973). In addition to aiding in migration, a larger body size may provide a reproductive benefit as postulated for I. argentinus, for which fecundity has been shown to increase with mantle length (Laptikhovsky and Nigmatullin, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, juveniles and mature females were not present in these samples. Winter cohorts were considered to be the primary source of recruitment to this fishery based on the seasonal distribution of paralarvae (Lu and Roper, 1979;Dawe and Beck, 1985;Dawe and Warren, 1993), length compositions (Squires, 1967;Coelho et al, 1994), and male maturation data (Mercer, 1973). However, this hypothesis was not confirmed by ageing studies of squid sampled from the Newfoundland fishery during 1982 and 1990 (Dawe and Beck, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In exploited squid populations, a g e and growth have sometimes been inferred from analysis of lengthfrequency distributions (e.g. Squires 1967, Summers 1971. Analysis of length-frequency distributions is usually futile for tropical and subtropical q u i d populations, which may spawn throughout the year, making length-frequency modes difficult or impossible to detect.…”
Section: Introductionmentioning
confidence: 99%
“…It is most likely that the IIlex sp. larvae from the winter surveys in this study were the products of spawning earlier in the winter, which, according to Squires (1967), is the major spawning season. Because of declining catches of larvae during the survey in January- March 1982, Hatanaka et al (1985 suggested that peak spawning in that year probably occurred in January.…”
Section: Larval Distributionmentioning
confidence: 78%
“…Aspects of the life history of this species are poorly understood, particularly its reproductive biology and longevity, in part because the time and location of spawning are unknown. Short-finned squid are believed to live for approximately 1 year (Squires, 1967) or 18 months (Mesnil, 1977) and to die after spawning. Spawning adults and egg masses have yet to be encountered in nature, but laboratory experiments have provided some insight into the processes of maturation and spawning, as well as embryonic and early larval development (O'Dor et al, 1977(O'Dor et al, ,1982O'Dor and Durward, 1978;Durward et al, 1980).…”
Section: Introductlonmentioning
confidence: 99%